Reseña/Review (Manovich, Lev, "Instagram and contemporary image", California Institute for Telecommunication and Information & The Graduate Center, City University of New York (CUNY): Cultural Analytics Lab, 148 págs., 2017) - Barrio Romera, Carla (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2018)
Reseña/Review (Manovich, Lev, "Instagram and contemporary image", California Institute for Telecommunication and Information & The Graduate Center, City University of New York (CUNY): Cultural Analytics Lab, 148 págs., 2017)